Causes and Consequences of miR-150-5p Dysregulation in Myasthenia Gravis - Cron, Mélanie A.; Maillard, Solène; Truffault, Frédérique; Gualeni, Ambra Vittoria; Gloghini, Annunziata; Fadel, Elie; Guihaire, Julien; Behin, Anthony; Berrih-Aknin, Sonia; Le Panse, Rozen (Frontiers in Immunology, 2019)
Autoimmune Myasthenia gravis (MG) is a chronic neuromuscular disease mainly due to antibodies against the acetylcholine receptor (AChR) at the neuromuscular junction, leading to invalidating muscle weaknesses. In early-onset MG, the thymus is the effector organ and is often characterized by B-cell infiltrations leading to ectopic germinal center (GC) development. The microRNA miR-150-5p has been previously characterized as a biomarker in MG due to its increase in the serum of patients and its decrease after thymectomy, correlated with an improvement of symptoms. Here, we investigated the causes and consequences of the miR-150 increase in the serum of early-onset MG patients. We observed that miR-150 expression was upregulated in MG thymuses in correlation with the presence of thymic B cells and showed by in situ hybridization experiments, that miR-150 was mainly expressed by cells of the mantle zone of GCs. However, we did not observe any correlation between the degree of thymic hyperplasia and the serum levels in MG patients. In parallel, we also investigated the expression of miR-150 in peripheral blood mononuclear cells (PBMCs) from MG patients. We observed that miR-150 was down-regulated, especially in CD4+ T cells compared to controls. These results suggest that the increased serum levels of miR-150 could result from a release from activated peripheral CD4+ T cells. Next, we demonstrated that the in vitro treatment of PBMCs with miR-150 or antimiR-150 oligonucleotides, respectively, decreased or increased the expression of one of its major target gene: the proto-oncogene MYB, a well-known actor of hematopoiesis. These results revealed that increased serum levels of miR-150 in MG patients could have a functional effect on PBMCs. We also showed that antimiR-150 caused increased cellular death of CD4+ and CD8+ T cells, along with the overexpression of pro-apoptotic genes targeted by miR-150 suggesting that miR-150 controlled the survival of these cells. Altogether, these results showed that miR-150 could play a role in MG both at the thymic level and in periphery by modulating the expression of target genes and peripheral cell survival.